A case control study of the factors associated with occurrence of aerodigestive foreign bodies in children in a regional referral hospital in South Western Uganda - Nakku, Doreen; Byaruhanga, Richard; Bajunirwe, Francis; Kyamwanga, Imelda T. (BMC Ear Nose Throat Disord, 2016)
Aerodigestive foreign bodies (ADFB) in children are a common emergency in ENT clinics globally. The aim of this study was to determine the prevalence and common types of ADFB’s presenting to a referral hospital in South Western Uganda, and to review clinical presentation and factors that influence their occurrence among children under 12 years of age.
Keywords: Aerodigestive, Foreign bodies, Factors, Occurrence, Uganda